Conformal Marked Bisection for Local Refinement of n-Dimensional Unstructured Simplicial Meshes. (January 2023) - Belda-Ferrín, Guillem; Ruiz-Gironés, Eloi; Gargallo-Peiró, Abel; Roca, Xevi
Abstract: We present an n -dimensional marked bisection method for unstructured conformal meshes. We devise the method for local refinement in adaptive n -dimensional applications. To this end, we propose a mesh marking pre-process and three marked bisection stages. The pre-process marks the initial mesh conformingly. Then, in the first n − 1 bisections, the method accumulates in reverse order a list of new vertices. In the second stage, the n -th bisection, the method uses the reversed list to cast the bisected simplices as reflected simplices, a simplex type suitable for newest vertex bisection. In the final stage, beyond the n -th bisection, the method switches to newest vertex bisection. To allow this switch, after the second stage, we check that under uniform bisection the mesh simplices are conformal and reflected. These conditions are sufficient to use newest vertex bisection, a bisection scheme guaranteeing key advantages for local refinement. Finally, the results show that the proposed bisection is well-suited for local refinement of unstructured conformal meshes. Highlights: A new multi-stage bisection for n-dimensional unstructured conformal meshes. Suitable for local refinement. Leads to conformal and reflected meshes after n uniform refinements. In the third stage, the method favors conformity, finiteness, stability, and locality.